2017
DOI: 10.1111/jvim.14792
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gallbladder Ultrasound Findings and Bacterial Culture of Bile in 70 Cats and 202 Dogs

Abstract: Background: Bacterial cholecystitis often is diagnosed by combination of gallbladder ultrasound (US) findings and positive results of bile culture. The value of gallbladder US in determining the likelihood of bile bacterial infection in cats and dogs with suspected biliary disease is unknown.Hypothesis/Objectives: To determine the value of gallbladder US in predicting bile bacterial culture results, identify most common bacterial isolates from bile, and describe complications after cholecystocentesis in cats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…23 The combination of collapse and gastrointestinal signs is a common clinical finding in dogs with anaphylaxis and was present in all of the cases in this report. 24 Moreover, elevated ALT and gall bladder wall abnormalities are described biomarkers for anaphylaxis in dogs. 24 All patients in this case series had an elevated ALT and three dogs had an ALT greater than 1000 U/l which was significantly associated with anaphylaxis in one report.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…23 The combination of collapse and gastrointestinal signs is a common clinical finding in dogs with anaphylaxis and was present in all of the cases in this report. 24 Moreover, elevated ALT and gall bladder wall abnormalities are described biomarkers for anaphylaxis in dogs. 24 All patients in this case series had an elevated ALT and three dogs had an ALT greater than 1000 U/l which was significantly associated with anaphylaxis in one report.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…24 Moreover, elevated ALT and gall bladder wall abnormalities are described biomarkers for anaphylaxis in dogs. 24 All patients in this case series had an elevated ALT and three dogs had an ALT greater than 1000 U/l which was significantly associated with anaphylaxis in one report. 24 Ultrasonographic evidence of an abnormal gall bladder wall was also present in three of four dogs.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…1,2,21 In addition to these findings, the current case displayed gall bladder wall thickening and echogenic gall bladder sediment, similar to cats in a case series reported by Brain et al 1 The presence of sonographic changes to the gall bladder has been demonstrated to be highly specific for gall bladder pathology, with cholecystitis and positive bile cultures identified in several studies. 1,[21][22][23] Diagnosis of neutrophilic cholangitis requires liver biopsy and histopathology. Bile culture is recommended to identify a causative agent and yields higher positive culture rates than culture of hepatic tissue (36% vs 16%).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs undergoing concurrent duodenotomy, hepatic duct bile was collected by passage of the catheter through the bile duct into an hepatic duct via the duodenal papilla. A swab sample of gallbladder content was collected intraoperatively by the attending surgeon and submitted to the NCSU-VH Clinical Microbiology laboratory for aerobic and anaerobic bacterial culture as previously described[ 27 ]. Gallbladder tissue was placed into formalin by the attending surgery technician and submitted to the NCSU-VH Histopathology laboratory for routine processing for light microscopic examination by the on-duty veterinary pathologist.…”
Section: Methodsmentioning
confidence: 99%